Mechanical canopy and trunk shaking for the harvesting mechanization of table olive orchards - Sola-Guirado, Rafael R.; Castillo-Ruiz, Francisco J.; Blanco-Roldan, Gregorio L.; Gonzalez-Sanchez, Emilio; Castro-García, Sergio (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
Table olive harvesting is highly dependent on manual labour and may jeopardize the crop benefit. The introduction of a mechanical harvest system requires a global evaluation of the whole process. A trunk shaker along with shaker combs and a continuous canopy shaker harvester have been tested in two orchards with different tree training and layout to determine their feasibility to mechanical harvesting in table olives. For that purpose, several parameters have been evaluated. Canopy shaker required adapted orchard layout and hedge of canopies for reaching an acceptable harvesting efficiency about 80% and trunk shaker performed a higher efficiency of more than 95% but depended highly on labour. Both systems had a high field capacity about 0.15 ha h-1 but low for the trunk shaker considering the people (0.01 ha h-1 person-1). The vibration pattern that applied on branches was totally different although the quantitative tree damages were no significative different. There were no significant differences in fruit bruising between both systems, but there were between the different sampling points, mainly in the detachment. The fruit bruising index of the remaining fruit on canopy suggests that it is possible to perform a second harvest. Both mechanical systems are suitable for table olive harvesting whilst improving the efficiency of manual systems with bearable damages, but each one has pros and cons that must be considered bearing in mind that require an adaptation of the orchard where there are applied. Highlights Table olives mechanization is possible by integrating with the fruit liquid store. Trunk shaker performed high efficiency in adapted orchards but depended on labour. Canopy shakers require the adaption of orchard and machine for commercial purposes. There were no differences in detached fruit bruising between both mechanical systems. The bruising index of the remaining fruit on trees suggest second harvesting pass.